Extraction and bioconversion of aroma impact compounds from Sauvignon Blanc grapes to wine matrices during white wine production - Greyling, Isabel (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.